Aristotelian neothomism in the 20th century: Charles de Koninck and differentiation of sciences of nature - Oleksandra Sakovska (Cхід, 2019)
The article is dedicated to the ideas of aristotelian neothomism representative Charles De Koninck, who was well-known philosopher and theoretician of science in neothomostic philosophical circles but ideas of who are still not examined enough. Charles De Koninck has initiated the whole new neothomistic movement, which was represented by Laval (Quebec, Canada) and River Forest (Chicago, the USA) schools. The article is aimed to demonstrate the tight connections between medieval and modern philosophies in the frame of Thomism, as well as to clarify the ideas of De Koninck in respect to differentiation of scientific disciplines on the basis of Aquinas teaching. By means of method of comparison, it was proved, that De Koninck uses the same arguments in respect to the difference between math, metaphysics and natural science, as Aquinas used in his 13th century. Still, the main contradiction between two approaches appears to be in the fact, that in Aquinas these three disciplines are represented in hierarchy, where metaphysics is a supreme, and still they are separated. At the same time, De Koninck neglects metaphysics as the less dependable knowledge, but uses physics instead. The article clarifies the approach of De Koninck regarding the notion abstraction of matter which appears to be the most significant reason of understanding both: unity and separation of sciences. The main purpose of De Koninck was to return philosophy (philosophy of nature in particular) into the science and to prove that no real knowledge can be possible only through experiments and contingent data of material world collection. This approach remained unchanged for the whole further aristotelian neothomism, as well as an idea that natural sciences are superior to metaphysics, specifically in order of obtaining knowledge. De Koninck’s teaching became quite influential among his student and highly beneficial to Catholic philosophy of  the North America.